Efektifitas Kelas Online Calon Ibu Terhadap Waktu Pencapaian Adaptasi Psikologis (Letting Go) pada Ibu Postpartum - Yuliana, Wahida; R.R., Retno Hastri; Hakim, Bawon Nul (Jurnal Kebidanan Malakbi, 2024)
Mothers in the postpartum phase need to adapt to the psychological changes that occur after childbirth. The phase of adaptation, called letting go is crucial for mothers to be able to embrace their new role. Failure to adapt to these psychological changes can lead to disorders such as depression, which can occur in 3.5% to 63.3% of cases. To address this issue, a study was conducted to analyze the effectiveness of online classes for expectant mothers in achieving psychological adaptation (letting go) during the postpartum period. The research was designed as a quasi-experimental study. The sample population consisted of all third-trimester primigravida pregnant mothers in Paiton Village, Probolinggo, totaling 30 mothers. The research sampling technique was total sampling. The data was analyzed using the chi-square statistical test (α=0.05). The results showed that 50% of the 30 respondents who were given an online class for prospective mothers were able to achieve psychological adaptation of letting go within 10 days. The analysis showed that the online class for prospective mothers had a significant effect on the timing of achieving psychological adaptation with p value <0.05. The study concluded that online classes for expectant mothers can be effective in helping mothers adapt to their new role more quickly. This research contributes to knowledge enhancement techniques for postpartum mothers in dealing with psychological adaptation.